The Influence of Teachers’ Competency and Organizational Culture on Teachers’ Performance - Jamila, Jamila; Arafat, Yasir; Kesumawati, Nila (Journal of Social Work and Science Education, 2025)
This study examines the influence of teachers’ competency and organizational culture on teacher performance in state senior high schools in Cengal District. A quantitative approach was employed using questionnaires, observations, and documentation to collect data from 42 teachers. Analysis using simple and multiple regression techniques in SPSS 26 revealed that teachers’ competency significantly influences performance (R² = 46.3%), while organizational culture also has a moderate influence (R² = 40.4%). Combined, these variables account for 68.1% of the variance in teacher performance. These findings underscore the importance of professional development programs and fostering a strong organizational culture to improve educational outcomes.